Eurosceptics into the Limelight? Eurosceptic Parliamentary Actors and Media Bias in EU Affairs - Auel, Katrin (2019)
In the spotlight for some time now, the potential of national parliaments to legitimise EU politics has become even more salient given the growing politicisation and public contestation of EU issues. Their ability to realise this potential depends, however, vitally on citizens being actually aware of parliamentary involvement in EU affairs. Academic as well as political attention has therefore more recently turned to the communication function of parliaments, and here the media play a crucial role. Important is not only whether EU parliamentary affairs are covered in the media, but also who within parliament gets the opportunity to raise European issues in the media. In the context of this thematic issue, the question of media visibility is of particular interest with regard to Eurosceptic parliamentary party groups and their members. Do Eurosceptics in parliament get to dominate parliamentary EU news in the media and thus to take ownership of EU issues—or do the media freeze parliamentary Eurosceptics out of the coverage? Both would seriously undermine the legitimising potential of national parliaments. The article therefore analyses to what extent we can find a visibility bias in the print media coverage of Eurosceptic parliamentary actors and explores the factors that contribute to such bias. For the analysis, it draws on a quantitative dataset of all newspaper articles covering parliamentary EU affairs in six member states (Austria, Finland, France, Germany, Poland and the UK) over a period of four years (2010 to 2013).